PENGEMBANGAN PERANGKAT PEMBELAJARAN JOB SHEET BERBASIS PERFORMANCE ASSESSMENT UNTUK MENINGKATKAN KOMPETENSI CONVENTIONAL ENGINE TUNE UP - Devi, Putri Laxmita; Wjiaya, M. Burhan Rubai; Suwahyo, Suwahyuo (Sainteknol : Jurnal Sains dan Teknologi, 2017)
This research aims to determine the feasibility of job sheet based performance assessment as learning device and to know increasing competence of student in conventional engine tune up learning. Data in this research were obtained using observation, questionnaire, tests and documentation methods. The results of feasibility analyses showed that job sheet get score 95.51% from expert validator, so it is feasible to use in theory. In addition, empirically using of job sheet can enhance competence of students from 33.33% to 80.56%. It can be concluded that job sheet based performance assessment is feasible to enhance competence of students. Thus, it is recommended as learning device to support practical learning. Â